Epidemiological and clinical characteristics analysis of 11 children with 2019 novel coronavirus infection in Chongqing: a single-center retrospective study - Chen, Qiang (Transl Pediatr, 2020)
BACKGROUND: The global epidemic of the 2019 novel coronavirus (2019-nCoV) is still going on. This article shares information about the infected children from a treatment center in Chongqing, China. METHODS: A retrospective analysis of the epidemiology, clinical symptoms, signs, laboratory examinations, chest computed tomography results, treatment effect of 11 children infected by 2019-nCoV was performed. Children were diagnosed from January 25 to February 29, 2020 in Chongqing University Three Gorges Hospital. RESULTS: The mean age of the 11 children with 2019-nCoV infection was 11 years and 5 months. Two cases (18%) were imported cases from Wuhan. The 9 cases (82%) were family cluster cases. There were 5 asymptomatic type cases (45%), 2 mild cases (18%), and 4 common type cases (37%). The most common symptom was fever (5 cases), cough (3 cases), sore throat (1 case) and diarrhea (1 case). There were abnormal chest CT changes in 6 cases, including 4 cases with patchy ground-glass opacities and 2 cases with thickened lung texture. Laboratory tests showed that procalcitonin increased in 4 cases (36%), and C-reactive protein (CRP) increased in 1 case (9%). In lymphocyte subgroup examination, lymphocyte count increased in 2 cases (18%) and decreased in 1 case (9%); T%, cluster of differentiation 8 (CD8)+ T%, and natural killer (NK) cell% were normal in 11 cases; CD4+ T% was increased in 2 cases (18%), and CD4+ T%/CD8+ T% was decreased in 1 case (9%); B% was increased in 1 case (9%). The interleukin 4 (IL-4), IL-10, and IL-17 in 11 cases were normal; IL-6 was increased in 7 cases (64%); tumor necrosis factor-alpha (TNF-α) was increased in 1 case (9%); and interferon gamma (IFN-γ) was increased in 6 cases (55%). All patients had been discharged from the hospital. CONCLUSIONS: Children are generally susceptible to 2019-nCoV, and the main way of infection is close contact with an infected person in the family. Clinical symptoms are mild. Laboratory and chest CT examinations are not as typical as those of adults. The prognosis is generally good. The unique immune function of children may help fight the new coronavirus.